VARIABILITY OF SOME MECHANICAL PROPERTIES OF SAN RAMON TALL VARIETY OF COCONUT - R. N. Palomar (International Coconut Community Journal, 1994)
The natural variation of some strength properties of about 80‑year old brown‑and green‑pigmented San Ramon variety of coconut was investigated. The properties were determined from tests on small clear specimens in the air dry condition with an average moisture content of 16.98%. The mechanical properties studied include modulus of rupture, stress at elastic limit and modulus of elasticity in static bending, maximum crushing strength in compression parallel to grain, stress at elastic limit and in compression perpendicular to grain, and shear parallel to grain. The brown‑pigmented trees showed significantly higher values in all the mechanical properties than the green‑pigmented palms. For the brown‑and green‑pigmented trees, the values of strength properties markedly decreased with increasing height levels and significantly increased radially from the core to the periphery of the stem.